Associations Between Types of Balance Performance in Healthy Individuals Across the Lifespan: A Systematic Review and Meta-Analysis - Kiss, Rainer; Schedler, Simon; Muehlbauer, Thomas (Frontiers in Physiology, 2018)
Background: The objective of this systematic review and meta-analysis was to quantify and statistically compare correlations between types of balance performance in healthy individuals across the lifespan. Methods: Literature search was performed in the electronic databases PubMed, Web of Science, and SPORTDiscus. Studies were included if they investigated healthy individuals aged ≥6 years and reported measures of static/dynamic steady-state, proactive, and/or reactive balance. The included studies were coded as follows: age group, gender, and balance type, test, parameter. Pearson's correlation coefficients were extracted, transformed (i.e., Fisher's z-transformed rz-value), aggregated (i.e., weighted mean rz-value), back-transformed to r-values, classified according to their magnitude, and statistically compared. The methodological quality of each study was assessed using the Appraisal tool for Cross-Sectional Studies. Results: We detected twenty-six studies that examined associations between types of balance and exclusively found small-sized correlations, irrespective of the age group considered. More specifically, the weighted mean rz-values amounted to 0.61 (back-transformed r-value: 0.54) in old adults for the correlation of dynamic steady-state with proactive balance. For correlations between dynamic and static steady-state balance, the weighted mean rz-values amounted to 0.09 in children (r-value: 0.09) and to 0.32 in old adults (r-value: 0.31). Further, correlations of proactive with static steady-state balance revealed weighted mean rz-values of 0.24 (r-value: 0.24) in young adults and of 0.31 (r-value: 0.30) in old adults. Additionally, correlations between reactive and static steady-state balance yielded weighted mean rz-values of 0.21 (r-value: 0.21) in young adults and of 0.19 (r-value: 0.19) in old adults. Moreover, significantly different correlation coefficients (z = 8.28, p < 0.001) were only found for the association between dynamic and static steady-state balance in children (r = 0.09) compared to old adults (r = 0.31). Lastly, we detected trivial to considerable heterogeneity (i.e., 0% ≤ I2 ≤ 83%) between studies. Conclusions: Our systematic review and meta-analysis showed exclusively small-sized correlations between types of balance performance across the lifespan. This indicates that balance performance seems to be task-specific rather than a “general ability.” Further, our results suggest that for assessment/training purposes a test battery/multiple exercises should be used that include static/dynamic steady-state, proactive, and reactive types of balance. Concerning the observed significant age differences, further research is needed to investigate whether they are truly existent or if they are caused by methodological inconsistencies.